Thrust Force and Delamination Analysis on Redmud-Filled Coconut Sheath Fiber Polyester Composite - Sundarakannan Rajendran; Yo-Lun Yang; Uthayakumar Marimuthu; Arumugaprabu Veerasimman; Geetha Palani; Karthick Babu; Vigneshwaran Shanmugam (Mechanics of Advanced Composite Structures, 2025)
Developing customized drilling processes that minimize damage and improve overall performance in natural fiber composites relies on a thorough understanding of their drilling performance and potential damages. This study explores the variations in delamination and thrust force in a redmud-filled polyester composite reinforced with coconut sheath fibers. Employing a Taguchi factorial design, the experiment investigates the impact of drilling parameters, including drill diameter, spindle speed, and feed rate. The ANOVA analysis is employed to validate the experimental results. The findings indicate that increased feed rates and spindle speeds contribute to elevated thrust forces and delamination, influenced by the composite's inherent brittleness due to the addition of red mud. Among the drilling parameters, feed rate exerts the most significant influence on thrust force (ca. 30%), while the point angle has the greatest impact on delamination (ca. 60%). The analysis of drilled hole surfaces reveals matrix cracks, fiber extraction, and matrix smearing, underscoring the importance of optimizing drilling parameters, selecting appropriate tools, and implementing effective cooling methods to improve the overall surface finish and quality of drilled fiber composites. The research has the potential to aid in the development of strategies to minimize damages and enhance overall surface quality; ultimately, it contributes to advancing knowledge in materials science and engineering, with applications in the manufacturing and utilization of natural fiber composites across diverse industries.